2015
DOI: 10.1242/jcs.160259
|View full text |Cite
|
Sign up to set email alerts
|

Myosin5a mediates BDNF-induced postendocytic recycling of full-length TrkB and its translocation into dendritic spines

Abstract: Brain-derived neurotrophic factor (BDNF) plays an important role in neuronal survival, neurite outgrowth and synaptic plasticity by activating the receptor tropomyosin receptor kinase B (TrkB, also known as NTRK2). TrkB has been shown to undergo recycling after BDNF stimulation. We have previously reported that full-length TrkB (TrkB-FL) are recycled through a Rab11-dependent pathway upon BDNF stimuli, which is important for the translocation of TrkB-FL into dendritic spines and for the maintenance of prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…S1C). To verify the results seen in genetically modified cells, we exposed cultured neurons to recombinant WW domain fused to the trans-activator of transcription (TAT) tag (TAT-WW), which we and others have previously established would enter spines directly, very rapidly, and with minimal toxicity (10, 14, 15). TAT-WW functions as a dominant-negative, preventing endogenous Pin1 from binding to target proteins (16).…”
Section: Resultsmentioning
confidence: 99%
“…S1C). To verify the results seen in genetically modified cells, we exposed cultured neurons to recombinant WW domain fused to the trans-activator of transcription (TAT) tag (TAT-WW), which we and others have previously established would enter spines directly, very rapidly, and with minimal toxicity (10, 14, 15). TAT-WW functions as a dominant-negative, preventing endogenous Pin1 from binding to target proteins (16).…”
Section: Resultsmentioning
confidence: 99%
“…Rab11 is important for developmental axon growth but its axonal presence is diminished with maturity, being difficult to detect in mature CNS axons, instead localizing principally in the somatodendritic domain (Koseki et al, ; Sheehan et al, ). In adult neurons Rab11 is involved in the regulation of post‐synaptic plasticity, with roles in receptor recycling (AMPA and TrkB receptors), dendritic spine development, and synapse structure (Correia et al, ; Lazo et al, ; Esteves da Silva et al, ; Sui et al, ). Conversely, there is less evidence for a presynaptic role for Rab11 in mammalian CNS neurons, although it has been observed at low levels in the synaptic vesicle fraction of synaptosomes.…”
Section: Developmental Decline In Axon Transportmentioning
confidence: 99%
“…TrkB is similar to the IGF receptor in that it too is involved in developmental axon growth (Gates et al, ), has been targeted to promote CNS regeneration (Plunet et al, ; Kwon et al, ; Hollis et al, ), and is transported in Rab11 endosomes. The recycling of TrkB receptor through Rab11‐positive recycling endosomes regulates its neuronal localization, and in mature neurons is involved in post‐synaptic receptor recycling in dendrites (Huang et al, ; Lazo et al, ; Sui et al, ). This is in contrast to its developmental enrichment at the growth cone of CNS neurons, from where it stimulates axon growth.…”
Section: Growth Machinery At Low Levels In Mature Cns Axons (Rab11 Anmentioning
confidence: 99%
“…In addition to the endolysosomal pathway, neurotrophin receptors are also sorted into Rab11‐positive recycling endosomes in an activity dependent manner . Recent studies have shown that this recycling process is less prevalent for the truncated form of TrkB (T1) than for full‐length TrkB, suggesting that it is regulated by the intracellular domain of the receptor, as well as by the interaction of TrkB with Slitrk5 via their extracellular domains, which affects receptor recycling and response to BDNF …”
Section: Signalling Endosomes Localize and Control Cellular Signallingmentioning
confidence: 99%